Anthropogenic and natural CO2 exchange through the Strait of Gibraltar ... : CO البشري والطبيعي < sub>2 </ sub> التبادل عبر مضيق جبل طارق ... - I. Emma Huertas; Aida F. Rı́os; Jesús García‐Lafuente; Ahmed Makaoui; Susana Rodríguez-Gálvez; Antonio Sánchez Román; A. Orbi; Javier Ruiz; Fíz F. Pérez (OpenAlex, 2009)
Abstract. The exchange of both anthropogenic and natural inorganic carbon between the Atlantic Ocean and the Mediterranean Sea through Strait of Gibraltar was studied for a period of two years under the frame of the CARBOOCEAN project. A comprehensive sampling program was conducted, which was design to collect samples at eight fixed stations located in the Strait in successive cruises periodically distributed through the year in order to ensure a good spatial and temporal coverage. As a result of this monitoring, a time series namely GIFT (GIbraltar Fixed Time series) has been established, allowing the generation of an extensive data set of the carbon system parameters in the area. Data acquired during the development of nine campaigns were analyzed in this work. Total inorganic carbon concentration (CT) was calculated from alkalinity-pHT pairs and appropriate thermodynamic relationships, with the concentration of anthropogenic carbon (CANT) being also computed using two methods, the ΔC* and the TrOCA ... : الخلاصة: تمت دراسة تبادل الكربون غير العضوي البشري والطبيعي بين المحيط الأطلسي والبحر الأبيض المتوسط عبر مضيق جبل طارق لمدة عامين في إطار مشروع CARBOOCEAN. تم إجراء برنامج شامل لأخذ العينات، والذي تم تصميمه لجمع العينات في ثماني محطات ثابتة تقع في المضيق في رحلات بحرية متتالية موزعة بشكل دوري على مدار العام من أجل ضمان تغطية مكانية وزمنية جيدة. نتيجة لهذا الرصد، تم إنشاء سلسلة زمنية وهي GIFT (سلسلة GIbraltar Fixed Time)، مما يسمح بتوليد مجموعة بيانات واسعة من معلمات نظام الكربون في المنطقة. تم تحليل البيانات التي تم الحصول عليها خلال تطوير تسع حملات في هذا العمل. تم حساب إجمالي تركيز الكربون غير العضوي (CT) من أزواج القلوية- PHT والعلاقات الديناميكية الحرارية المناسبة، مع حساب تركيز الكربون البشري (CANT) أيضًا باستخدام طريقتين، نهج ΔC* و TrOCA. بتطبيق نموذج من طبقتين لتبادل كتلة المياه عبر المضيق وباستخدام قيمة -0.85 Sv لمتوسط نقل مياه البحر الأبيض المتوسط المتدفقة المسجلة في الموقع خلال الفترة المدروسة، تم الحصول على تصدير صافٍ للكربون غير العضوي من البحر الأبيض المتوسط إلى المحيط الأطلسي، والذي بلغ 25±0.6 ...